2020
DOI: 10.1017/s143192762000183x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Blind Deconvolution Based on the New Weighted L1-norm Regularization with Alternating Direction Method of Multipliers in Light Microscopy Images

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…From the visual evaluation of the resulting image, it was confirmed that the sharpness of the deblurred image was improved compared with that of the degraded image in all areas of the tooth, PDL, and bone. Here, the deblurred image was generated by applying the previously l 0 -norm-based blind deconvolution method [49] to compare the results of the proposed method. Noise amplification in the deblurred image occurred significantly in all areas, and the noise level of the image could be reduced using the denoising method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the visual evaluation of the resulting image, it was confirmed that the sharpness of the deblurred image was improved compared with that of the degraded image in all areas of the tooth, PDL, and bone. Here, the deblurred image was generated by applying the previously l 0 -norm-based blind deconvolution method [49] to compare the results of the proposed method. Noise amplification in the deblurred image occurred significantly in all areas, and the noise level of the image could be reduced using the denoising method.…”
Section: Resultsmentioning
confidence: 99%
“…When using an objective function to obtain a deblurred image from a noisy image, it was difficult to give much weight to the regularization term due to increase the possibility of obtained the smoothing results. To overcome this limitation, our previous study demonstrated that proposed approach by setting the regularization term based on weight map and l 1 -norm improved the sharpness of image without cartoonish artifact [49]. The l 0 -normbased deconvolution method without weight function was applied to the deblurred image for improving the resolution.…”
Section: Proposed Restoration Scheme For Microscopic Imagesmentioning
confidence: 99%
“…Optimization methods also find applications in microscopy, for example [129][130][131][132][133]. Their shortcomings are not so critical for this area, since the optical schemes correspond much more strictly to the concept of a linear spatially invariant system.…”
Section: Optimization-based Deconvolution Methodsmentioning
confidence: 99%
“…Regularization [1,3] is to add structured risk to experience risk or experience loss. In this paper, the structured risk parameter is penalized by norm, which is used to limit the learning ability of the model and improve the generalization ability by preventing high deviation.…”
Section: Mathematical Models Formulationmentioning
confidence: 99%
“…For short-term load power forecasting, scholars have proposed a large number of power forecasting methods, including but not limited to neural network method, Markov chain method, support vector machine and so on [3]. Although the above algorithms have their own advantages and disadvantages, they are all based on massive data for target prediction and analysis.…”
Section: Introductionmentioning
confidence: 99%